Ecology and Diversity of Phytoplankton in the Great Kwa River, Cross River State, Nigeria - Eyo, Victor Oscar; Ekpo, Paul Bassey; Andem, Andem Bassey; Okorafor, Kalu A. (International Journal of Fisheries and Aquatic Studies, 2013)
This Ecology and diversity of phytoplankton in the Great Kwa River, Nigeria was studied based on bi monthly samples collected for six months (May to October, 2012). The objective of the study was to determine the abundance and species composition of phytoplankton from four sampling stations in the study area. A total of eighty-nine (89) species of phytoplankton belonging to six (6) taxonomic groups were recorded: 1 Dinophyceae (1.12%), 3 Chrysophyceae (3.37%), 4 Euglenophyceae (4.50%), 9 Cyanophyceae (10.11%), 23 Chlorophyceae (25.84%) and 49 Bacillariophyceae (55.06%). Total number of phytoplankton species in the study area in relation to sampling station was highest in Esuk Atu with 77 species (27.70%), followed by 71 species in Anantigha station (25.54%), followed by 69 species in Bofa Esuk station (24.82%) and lowest in Abitu station with 61 species (21.94%). Ten (10) absolutely constant species (AS) were found in Bacillariophyceae and none in Chrysophyceae, Cyanophyceae, Dinophyceae and Euglenophyceae. Species diversity indices were quite impressive in the four sampling stations leading to the conclusion that the Great Kwa River is in a healthy and unpolluted state.
Keywords: Diversity; Species Composition; Phytoplankton; Great Kwa River; Sampling Stations.